The failure of substrate pKa to influence the microsomal formation of amides from N-benzylamines: The microsomal metabolism of N-benzyl pyrrolidine, N-benzyl carbazole and N-acetyl-N-benzyl-4-methylaniline - (:unkn) unknown (ROYAL PHARMACEUTICAL SOC GREAT BRITAIN, 1996)
The in-vitro hepatic microsomal metabolism of N-benzylpyrrolidine (NBP), N-benzylcarbazole (NBC) and N-acetyl-N-benzyl-4-methylaniline (NANBMA) has been studied, using hamster microsomal preparations, to establish whether the corresponding amide is formed. Amide formation was not observed with any of the substrates utilized, although several metabolic products were detected by HPLC with UV detection. These included the oxidative debenzylation products (for all substrates), ring hydroxylated products (for NBC) and a lactam metabolite (for NBP). The results support the concept that the metabolic conversion of benzylic amines to the corresponding amide involves an N-oxidative step.
Keywords: OXIDATION; BENZYLANILINES; DEMETHYLATION; INTERMEDIATE; NICOTINE; ION